(untitled) (KYAMC Journal, 2017)
Introduction: Addison’s disease is a relatively rare endocrine condition requiring life-long glucocorticoid and mineralcorticoid replacement therapy. Women with Addison’s disease may have a reduced parity. Addisonian crises, a rare but life-threatening event in pregnant women, may accompany stressful conditions such as labor, puerperium, infection, hyperemesis gravidarum or surgery. Case Presentation: This is a case report of previously healthy 24-year-old nulliparous woman presented with a history of fatigue, fever, diarrhoea and skin darkening. She had pale conjunctiva, low blood pressure, tachycardia, some dehydration, hyperpigmentation of palmer creases, knuckles, buccal mucosa and face. Her serum cortisol was low and rapid ACTH stimulation test with Synacthen showed a poor cortisol response. Patient was immediately managed with IV steroid and later dicharged with oral steroid. After 6 months she became pregnant and the steroid therapy was regulated to avoid adrenal crisis during pregnancy. The patient underwent to caesarean section at 38th week and gave birth to a normal baby. Conclusion: Addisonian crisis represents an endocrine emergency that requires a correct diagnosis with prompt and appropriate salt and steroid replacements to save the patient. Though Addison’s disease in women is a risk factor for an adverse pregnancy outcome, it is believed that appropriately treated patients can expect to have uneventful pregnancies of normal duration and without fetal compromise. KYAMC Journal Vol. 7, No.-2, Jan 2017, Page 814-817